Polypharmacy in Zoological Medicine - Robert P. Hunter; Ramiro Isaza (MDPI AG, 2017)
Polypharmacy is a term that describes the inappropriate, concurrent use of multiple drugs in an individual patient. Zoological medicine practitioners must take approved agents (veterinary or human) and extrapolate their use to non-approved species often with little species-specific pharmacological evidence to support their decisions. When considering polypharmacy, even less information exists concerning multi-drug pharmacokinetics, pharmacodynamics, or potential drug-drug interactions in non-domestic species. Unfortunately, captive, zoological species are susceptible, just like their domestic counterparts, to chronic diseases and co-morbidities that may lead to the usage of multiple drugs. Polypharmacy is a recognized and important issue in human medicine, as well as an emerging issue for veterinarians; thus, this paper will discuss the novel, potential risks of polypharmacy in zoological medicine. Hopefully, this discussion will help bring the attention of veterinarians to this issue and serve as an interesting discussion topic for pharmacologists in general.